Can tourism qualify for interdisciplinary research? A European view - Pechlaner, Harald; Volgger, Michael (2015)
This paper adopts a political perspective on the disciplinary status of research on tourism and postulates that in "declaring" itself to be on the way towards becoming "a discipline", tourism research could significantly gain and uphold the recognition by policy and industry. This will not call into question the fact that methodological and content criteria ought to be considered and respected, however. Declarations should endeavour to be accepted not only within by the members of the tourism community but also externally. It should clarify that "becoming an academic discipline" is a scenario that could provide a number of opportunities for tourism research. Academic disciplines as distinct segments of knowledge have always contained a political aspect with political implications and it is this dimension that we intend to emphasize.